Evolution of joint power across the lifespan during walking - Bernard X. W. Liew; Rachel Senden; David Rugamer; Kenneth Meijer; Qichang Mei; Kim Duffy; Kevin Netto; Matthew Taylor (Journal of NeuroEngineering and Rehabilitation)
Abstract Objectives To determine the evolution of lower-limb joint power values during walking across the lifespan. Design Series of cross-sectional studies. Setting This was a pooled analysis of the individual participant joint power data from six datasets, resulting in a sample size of 629 participants, between the ages of three to 91 years old. Main outcome measures Three function-on-scalar regression models were fitted on the outcome measures of joint hip, knee, and ankle power. The covariates of this analysis included sex, age, walking speed, stride length, height, the interaction between age and speed, and a random intercept for different studies. Results Ankle push-off (A2) power peaked with a value of 2.46 (95%CI 2.41 to 2.50) W/kg in the 3rd decade of life. Hip early-stance power (H1) peaked in the 1st decade, which followed a sharp decline with age till the 3rd decade. Hip pull-off power (H3) increased sharply to 0.86 (95%CI 0.84 to 0.88) W/kg in the 5th decade and stabilised thereafter with older age. Conclusion Ankle push-off power appears to reach maturity in the 3rd decade of life. A strict temporal correspondence between a decline in ankle push-off power (A2) with age and a compensatory increase in hip pull-off power (H3) was not observed, challenging the distal-to-proximal alteration in propulsion strategy commonly attributed to the ageing process.